#TITLE_ALTERNATIVE# - MARTIN HUTAPEA (NIM : 13204201); Pembimbing : Prof. Dr. Ir. Ngapuli Irmea Sinisuka, PHILIP
Load forecasting is vitally important for the electric industry in deregulated economy. It has many aplications including energy purchasing and generation, contract evaluation, and infrastructure development. This final project research gives a model for spatial electric load forecasting based on regression method. Division of the area into small areas is done based on clustering with hierarchy technic. The loads in the small area are the total load of all distribution transformers that are placed in the area. The future load forecasts are done with regression. The transformer management analysis is done as an ilustration to the aplication of the load forecastingÃ‚Â’s function in distribution system. The spatial load forecasting model are applicated and gives a fair good results. The model are able to give the information about the spread of the load geographically in the distribution system area for ten years ahead period. The accuracy of the model are appraised from the goodness of fit and give result for the mean percentage residual (MPR) = -0,3670%, and mean absolute percentage residual (MAPR) = 7,1555%.